Metode Hand On Cooking untuk Meningkatkan Keterampilan Praktik Boga Dasar Siswa Kelas X SMK Negeri 6 Surabaya - Sheren Aurora Maharani; Diana Evawati; Winijarti, Winijarti; Adisti Putri Permatasari; Aprillia Ayu Nastiti (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to improve students' basic culinary practice skills through the application of the hands-on cooking method. The research method used is Classroom Action Research (PTK), which is carried out in two cycles. Data collection techniques are carried out through observation and skill tests, with instruments in the form of observation sheets and test questions that have been validated by experts. Data analysis is carried out descriptively and quantitatively to see the increase in students' skills from pre-cycle to cycle II. The results of the study showed a significant increase in basic culinary practice skills. At the pre-cycle stage, the average student skills were at 54.56% with (fair category). After the hands-on cooking method was applied, the average value increased to 67.38% (good category) in cycle I, and reached 81.06% (very good category) in cycle II. The conclusion of this study is that the hands-on cooking method is proven to be effective in improving students' basic culinary practice skills. This method not only makes students more active in learning, but also helps them think creatively, face challenges, and develop problem-solving skills directly through practical experience in the field.